If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(6) = 1 + -2(6 + -1) Reorder the terms for easier multiplication: 6a = 1 + -2(6 + -1) Combine like terms: 6 + -1 = 5 6a = 1 + -2(5) Multiply -2 * 5 6a = 1 + -10 Combine like terms: 1 + -10 = -9 6a = -9 Solving 6a = -9 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '6'. a = -1.5 Simplifying a = -1.5
| 7n-4=38 | | 6u-12=u+3 | | 29=7(w+7)-3w | | a(9)=-3-4(9-1) | | 3V+6V-2=34 | | f(x)=6x-6 | | 85/100 | | 5u+8(u-7)=9 | | 65/85 | | 9x^6+42x^5+24x^4=0 | | 3(y+6)-8y=33 | | 56.8(5-2x)-(8x-9)=4 | | h-17=19 | | a(13)=-7+6(13-1) | | 8x-6y^2-8=0 | | y^4=18 | | 8x+6y^2-8=0 | | 3=v/2 | | 8x-6x^2=8 | | -2y(y+12)=y-9 | | a(11)=2-6(11-1) | | x+(.08x)=18.90 | | k/2=2 | | 8x-6x^2-8=0 | | X^6-37=0 | | 8x-6=5x-4.5 | | 11.20x+10.20y=428 | | X^4+x^2-2= | | w-11=2 | | 6y-x+7=0 | | 12a-2(5a-4)= | | 13=-4d |